Quantum theory of matter in bulk: Modern treatment - Manoukian, Edouard B.; Sukhasena, Seckson (Food Agricultural Sciences and Technology, 2016)
A systematic mathematical modern presentation is given, providing in a direct way the underlying technical details, to show how quantum theory, with the Pauli exclusion principle, has, over the years, solved the problem of why matter in bulk is stable and occupies so large a volume.